MANAJEMEN KONFLIK DALAM KEPEMIMPINAN PENDIDIKAN ISLAM - Faisal Dahrul Salihin (JGK (Jurnal Guru Kita), 2023)
Conflict Management in Leadership Islamic Education. This study aims to explain conflict management in Islamic educational leadership. The method used in this research is library research. The approach used is a qualitative approach. The study results show that one strategy that is appropriate in solving problems that occur in Islamic educational institutions is carried out by a leader of an Islamic educational institution who has a leadership spirit and a commitment so that problems in an educational institution can be resolved properly and efficiently. The way to manage conflict in Islamic education leadership is namely by negotiating or bargaining, tabayun, deliberation, tahkim, and islah.